Soya effects on post menopausal endometrial mucosa - Jara, Delia (2006)
Objective: To determine endometrial morphology and estrogen receptors expression changes in post menopausal women following oral soya treatment. Design: Descriptve, observational, longitudinal and prospective study. Setting: Pathology Institute, San Marcos National Major University. Patients: Twenty-two post menopausal women treated with soya. Interventions: Histological and immunohistochemical studies were done in endometrium aspiration biopsies before and after 6 months treatment with 60 g oral soya per day. Main outcome measures: Endometrium histology and estrogen and progesterone receptors expression changes. Results: Age ranged between 46 and 65 years, 53 years average. There was apparent vasomotor symptoms improvement. Endometrium before soya treatment was atrophic in 19 patients (86%) and inactive in 3 (14%). Following soya treatment 17 (77,3%) persisted atrophic, 4 (18,2%) were inactive and one became proliferative. Estrogen receptor expression was negative before soya treatment in 19 patients (86%) and 16 (76%) remained negative following treatment. Conclusions: Post menopausal women treated with soya during 6 months showed persistence of atrophic endometrium and negative expression for estrogen receptors